Paradigm shift in the management of mild asthma: Focus toward a patient centered approach. Issue 1 (2nd January 2020) - Satia, I.; Cusack, R. P.; O'Byrne, P. M.
Abstract: Asthma affects nearly 340 million people worldwide and over 50% of patients have mild asthma. The goals of treatment are to improve day-to-day asthma symptom control and to reduce the risk of exacerbations requiring systemic corticosteroids, and emergency department visits and hospitalizations. Airway inflammation and smooth muscle hyperresponsiveness are the pathophysiological hallmarks of asthma, but until recently, mild asthma treatment recommendations have relied on bronchodilators (short-acting inhaled β2 -agonists) alone and in step 2 the addition of regular inhaled corticosteroids. Unfortunately, paradoxical messages to patients relating to treatment steps has resulted in short acting β2 -agonists being the most commonly used inhaler for mild asthma and low adherence to inhaled regular corticosteroids. This concise review focuses on the pharmaceutical background and safety concerns of drugs for mild asthma, and reviews new evidence which has prompted a paradigm shift toward a patient centered approach. As needed low dose inhaled steroid with a long acting β2 -agonist is now the preferred controller and reliever medication for the treatment of mild asthma.